Accountability management system of superior elementary school for digital transformation - Triwiyanto, Teguh; Kusumaningrum, Desi Eri; Sobri, Ahmad Yusuf; Maitreepun, Warapark (Intelektual Pustaka Media Utama, 2024)
The purpose of this research is to find out i) the quality of the accountability management system of superior schools, ii) elementary school digital transformation capabilities, and iii) the relationship between the quality of the accountability management system for superior schools and the digital transformation capabilities of elementary schools in Indonesia. The research approach used is quantitative. The research location is in public elementary schools in Malang City. The population of this research is all 195 public elementary schools. The research sample is 22 public elementary schools. The research subjects were school principals, class teachers, and subject teachers totaling 51 people. Data collection is done by using a questionnaire. Elementary schools with superior school accountability management systems have the ability to drive their digital transformation capabilities. Excellent school accountability management systems and school digital transformation capabilities guarantee equal access to education for all students. Implications for improving teaching and learning are also discussed in this paper. The variables studied can be used to determine the priority scale for planning, implementing and evaluating superior school accountability management systems in digital transformation, in increasing teacher competency.